How to teach computer programming if our goal is the International Olympiad in Informatics - Király, Sándor (Teaching Mathematics and Computer Science, 2011)
Nowadays if a student in Hungary (age between 17-20 years old) wants to be the member of the Hungarian selected team (has four members) to participate in the International Olympiad in Informatics (IOI), first, he has to qualify himself in the first fifteen of the National Secondary School Competition (OKTV) in the programming category after the III. round. Then he should be in the first four place after the sixth round of the Selection Competition. Being successful is necessary that the student wants to start studying computer programming at least in the 9th school year and he needs a teacher who prepares him. In the last nine years three students of the author have participated in five Olympics and two of them won gold and bronze medals. This article wants to demonstrate the methods that a teacher needs to use to teach students in 9th school year for computer programming, to be the member of the Hungarian National Team after three or four years.